Modos de ser professor-artista (Revista Apotheke, 2022)
This article aims to point the positions about teaching-artistic from the concept of deterritorialization, considering some experiences in the field of visual art teaching, in academic activities and the research as contributions to discuss about this theme. There are researcher reports from the author degree in Visual Arts, passing through the teaching experiences to arrive at the current moment that He develops on his Ph.D., with the focus on this topic discussed. In this text one can see that teaching and art as territorialities in a process of openness to deterritorialization and reterritorialization together in a new space. This new space is taken as a multiterritoriality, as well as encompasses teaching and art, it is open to other contaminations, to let it be affected by other territorialities that are interconnected.
Keywords: teaching-artistic; deterritorialization; multiterritorially